The role of episodic memory in imagining autobiographical events: the influence of event expectancy and context familiarity. Issue 5 (28th May 2022) - Fenerci, Can; Sheldon, Signy
ABSTRACT: Episodic memory plays a common role in constructing mental representations of past and imagined autobiographical events. Research has suggested that certain factors will affect how episodic memory is used during mental construction, such as the expectancy that an event will occur and the familiarity with an event's context. The aim of the current study was to understand how these factors affect episodic memory engagement and subjective experience during event imagination. In a within-subjects design, participants viewed context cues (high or low in familiarity), described imagined autobiographical events (expected or not expected to occur in these contexts) and rated their experience. 24-hours later, participants recalled and described the same events. We found that expectancy of the imagined events was associated with quicker access and increased episodic detail generation, regardless of context familiarity. Additionally, both event expectancy and context familiarity affected the subjective quality of the imagined events. Examining the episodic details in descriptions after the delay revealed comparable effects of these two factors. Our results underscore the importance of event expectancy in recruiting episodic memory for imagined autobiographical experiences.